Cultural & nature-based tourism corridors: pilot project at Terengganu Darul Iman - Hamzah, Amran; Abd. Kadir, Irhanida (Faculty of Built Enviroment, 2008)
Kelantan Darul Naim is a state blessed with many touristic attractions, unique art activities, mouth-watering dishes, the oldest tropical rainforest and the friendly nature of its people. With half of its coast facing the South China Sea and the land bordering Thailand in the north, Kelantan is also well-endowed with rich natural heritage that is definitely a feast for the eyes. Various cultural performances like the wayang kulit (shadow play) and dikir barat, as well as batik-painting, songketweaving and the making of other local handicraft are to be presented. The richness of tourism resources in Kelantan is possible to contribute to the income and local development of the local community by developing nature-culture based tourism corridor. In this study, it is aimed to bring up the nature-culture based tourism concept in Kelantan by evaluating the nature-culture based tourism industry in the state and assessing the natural-cultural resources that Kelantan comprehends. Market Appeal Model has been used to analyses the data that have been gathered in this study. The most important areas that have a nature-culture based tourism potential and the tourism activities that are most suitable for these areas have been determined and suitable tourism corridors have been proposed. `